Combating the challenges in adult learning: The case of Knust distance learners (Journal of Science and Technology, 2016)
Majority of distance education students are adults. Such people have many responsibilities; they have families, jobs, social life and other commitments. The ability to manage and co-ordinate their enormous activities will determine how successful they would be in their studies. The primary role of the student is to learn. The purpose of this paper was to find out The challenges faced by the students pursuing distance programmes at Kwame Nkrumah University of Science and Technology (KNUST) and how they are able to effectively manage them. To enable the students achieve this challenging task requires motivation, planning, and ability to analyse and apply the information being taught. Questionnaire was used to elicit information from a sample size of 120 students pursuing undergraduate and post graduate programmes at the Institute ofDistance Learning (IDL), KNUST. The study revealed that the challenges facing the students include how to combine their work with their studies, manage family and social activities. They are often misunderstood, isolated and some are contemplating dropping out from the programme.They also feel burdened with studies and do not know where to turn to for help. Recommendations were made on how the IDL could help the students to manage and co-ordinate their activities in order to go through their programmes successfully.